Shorebirds wintering in Southeast Asia demonstrate trans-Himalayan flights - David Li; Geoffrey Davison; Simeon Lisovski; Phil F. Battley; Zhijun Ma; Shufen Yang; Choon Beng How; Doug Watkins; Philip Round; Alex Yee; Vupasana Srinivasan; Clarice Teo; et al. (Scientific Reports, 2020)
Abstract Many birds wintering in the Indian subcontinent fly across the Himalayas during migration, including Bar-headed Geese (Anser indicus), Demoiselle Cranes (Anthropoides virgo) and Ruddy Shelducks (Tadorna ferruginea). However, little is known about whether shorebirds migrate across the Himalayas from wintering grounds beyond the Indian subcontinent. Using geolocators and satellite tracking devices, we demonstrate for the first time that Common Redshanks (Tringa totanus) and Whimbrels (Numenius phaeopus) wintering in Singapore can directly fly over the Himalayas to reach breeding grounds in the Qinghai-Tibet Plateau and north-central Russia respectively. The results also show that migratory shorebirds wintering in Southeast Asia can use both the Central Asian Flyway and the East Asian-Australasian Flyway. For Redshanks, westerly-breeding birds crossed the Himalayas while more easterly breeders on the Plateau migrated east of the Himalayas. For Whimbrels, an individual that crossed the Himalayas was probably from a breeding population that was different from the others that migrated along the coast up the East Asian-Australasian Flyway. The minimum required altitude of routes of trans-Himalayan Redshanks were no higher on average than those of eastern migrants, but geolocator temperature data indicate that birds departing Singapore flew at high elevations even when not required to by topography, suggesting that the Himalayan mountain range may be less of a barrier than assumed.